2007
DOI: 10.1111/j.1551-2916.2007.01547.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Loss Dielectrics in the Ca(B′1/2Nb1/2)O3 [B′=Lanthanides, Y] System

Abstract: The Ca(B′1/2Nb1/2)O3 [B′=La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Y, Er, Yb, and In] complex perovskites have been prepared by conventional solid‐state ceramic route. The structure and microstructure of the ceramics have been characterized by X‐ray diffraction and scanning electron microscopy methods. The ceramics have dielectric constant (ɛr) in the range 23–32, normalized Q‐factor (Qu×f) 11 000–38 000 GHz and temperature coefficient of resonant frequency (τf) −43–5.2 ppm/°C. The microwave dielectric properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The relationship between tolerance factor and phase transition can also be applied in other perovskite systems. 21 Different τ f can be observed frequently for the complex perovskites with the same t value. Park et al 22 indicated that this difference could be understood by bond valence sum (BVS) in microwave dielectric ceramics with perovskite structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between tolerance factor and phase transition can also be applied in other perovskite systems. 21 Different τ f can be observed frequently for the complex perovskites with the same t value. Park et al 22 indicated that this difference could be understood by bond valence sum (BVS) in microwave dielectric ceramics with perovskite structure.…”
Section: Introductionmentioning
confidence: 99%
“…further ascertained that for Ba‐ and Sr‐based complex perovskites, the first phase transition occurs around t = 0.985, and the other phase transition occurs around t = 0.965. The relationship between tolerance factor and phase transition can also be applied in other perovskite systems 21 . Different τ f can be observed frequently for the complex perovskites with the same t value.…”
Section: Introductionmentioning
confidence: 99%
“…Although several types of dielectric materials have been investigated to meet the requirements of microwave applications, those with perovskite or related structure are one of the most researched types for their extreme structural and compositional flexibility, such as simple perovskites ABO 3 , 1:2 ordered complex perovskites A 3 B′B″ 2 O 9 , and B‐site cation‐deficient hexagonal perovskites A n B n −1 O 3 n . In recent years, double perovskites with a general formula A 2 (B′B″)O 6 used as microwave dielectric materials have also attracted much attention …”
Section: Introductionmentioning
confidence: 99%
“…However, to obtain a high degree of ordering, prolonging high‐temperature sintering and soaking time or introducing small amounts of dopants is often necessary, which is not suitable for practical applications. Moreover, microwave dielectric properties of some 1:1 ordered perovskites with a general formula A 2 (B′B″)O 6 (A=Ba, Sr, Ca; B′=lanthanides and Y, B″=Nb, Ta) were also investigated 15–17 . It is concluded that ionic ordering driving force is favored by larger differences in charges and ionic radii between the two B‐site ions.…”
Section: Introductionmentioning
confidence: 99%